Portable HiRes Multi-Channel Seismic Shot Data from the Tjornes Fracture Zone, offshore Northern Iceland, acquired during the R/V Bjarni Saemundsson expedition BSTFZB9 (2001) ... - Detrick, Robert; Brandsdottir, Bryndis; Driscoll, Neal (Interdisciplinary Earth Data Alliance (IEDA), 2009)
This data set was acquired with the LDEO Portable HiRes Multi-Channel Seismic system during R/V Bjarni Saemundsson expedition BSTFZB9 conducted in 2001 (Chief Scientist: Dr. Robert Detrick; Investigators: Dr. Robert Detrick, Dr. Bryndis Brandsdottir, and Dr. Neal Driscoll). These data files are of SEGY format and include Multi-Channel Reflection Seismic shot data that have not been processed. Data were acquired as part of the project: Pilot Study of the Tjornes Fracture Zone, offshore Northern Iceland, using High-Resolution Multi-channel Seismic Reflection Profiling and CHIRP Sonar, and funding was provided by NSF grant: OCE01-14357. ...